APPLICATION OF LKPD BASED ON GUIDED INQUIRY MODEL ASSISTED BY PHET SIMULATION TO LEARNERS' CRITICAL THINKING SKILLS - Aswirna, Prima; Roza, Media; Aldania, Riska (Journal of Learning and Technology in Physics, 2024)
Learning in Indonesia does not encourage learners to think critically. Based on the results of the study states that learning in school has not been able to cultivate critical thinking skills in learners because learning still tends to be teacher-centered. The critical thinking skills of learners in the schools studied are still relatively low. Research from various researchers has previously stated that guided inquiry models can improve the ability of critical thinking pills. The purpose of this study is to find out if there is an influence on the critical thinking skills of learners who apply LKPD based on the guided inquiry learning model based on PhET Simulation compared to applying conventional PhET-assisted learning models only. This research is a pseudo-experiment using the Design Counter Balance. Data capture using the t-test. The results of the implementation of LKPD based on the PhET-assisted inquiry model show that there is an influence on the critical thinking skills of learners rather than conventional models with PhET.Keywords: LKPD, Guided Inquiry, PhET Simulation, and Critical thinking skills.